Challenges of Integrated Learning in Social Studies - Bhaskara, Esha (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to comprehensively identify and analyze various challenges in the implementation of integrated social studies instruction at the elementary and secondary education levels. The method used was a literature review involving the identification, screening, and selection of articles. Of the 148 articles identified, 15 met the inclusion criteria for further analysis. Data collection was conducted using keywords related to challenges, difficulties, and the implementation of integrated learning in social studies. The results of the study indicate that the main challenges include low priority in the curriculum, suboptimal integration of interdisciplinary content, limited instructional time, and insufficient resources and teaching materials. Additionally, teachers competencies in adapting to changes and utilizing educational technology still need to be improved. Internal and external factors related to students also influence learning difficulties, while the utilization of the environment and global issues as learning resources remains suboptimal. In conclusion, the success of integrated social studies learning requires strong curriculum policy support, enhanced teacher professionalism, and innovation in strategies and the utilization of contextual and adaptive learning resources.